Queen Berenice: a Jewish female icon of the first century CE - Ilan, Ṭal (Studies in theology and religion, 2022)
This is a biography of Queen Berenice, the daughter of King Agrippa I, sister of King Agrippa II, wife of two kings and lover of the emperor designate Flavius Titus. A Jew of the 1st century, she witnessed some of the foundational events of her time like the emergence of Christianity and the destruction of the Second Temple in Jerusalem, is. She met and socialized with the most important people of her day - Philo the Philosopher (who was at one time her brother-in-law), Paul the Apostle (whose trial she witnessed) and Josephus the Historian who told part of her story